The woman writer's body: Multiplicity, neoliberalism, and feminist resistance. Issue 1 (10th August 2021) - Quah, Sharon Ee Ling; Ridgway, Alexandra
Abstract: What goes behind the scene of a woman writer's writing process? Beneath shiny finished writing products lies an arduous writing process often remain unseen to readers. The article makes visible two women writers' bodies and our embodied writing experiences through an intersectional feminist lens. Writer One is a Singapore‐born, ethnic Chinese, queer migrant woman academic residing in Australia with her long‐term partner. Writer Two is an England‐born, Australian‐British dual citizen, white heterosexual married mother of young twin children ready to kick start her academic career after her recent PhD conferment. Writer One with her fibromyalgic, traumatized, and othered bodies and Writer Two with her vulvodynia, mothering, and gendered bodies write themselves, their bodies and embodied writing experiences into existence in this article. Using autoethnographic accounts, they discuss how their multiple, chronically ill, and pained bodies influence their writing process and choice of writing topics. Specifically, they reveal how their bodies negotiate the tension between neoliberal demands imposed on their bodies and their feminist resistance efforts against constrictive forces in the knowledge production economy. Using this piece of writing as feminist resistance, they seek to reject dominant discourses, hold space, inscribe their own narratives, and call for collective feminist action with fellow women writers.